24 PATENT FORAMEN OVALE; A MASQUERADER OF HYPOXIA IN RESPIRATORY FAILURE. (1st January 2006) - Sircar, P.; Godkar, D.; Gupta, A.; Niranjan, S.
Abstract : Background: Patent foramen ovale (PFO) is a common form of atrial septal defect where there is incomplete closure of the septum secundum, leaving a small residual opening. Very large ones can be detected in 25% of autopsies, while small defects (0.5-1.0 cm) are present in about 6%. Most patients with PFOs are asymptomatic; however in conditions giving rise to high right-sided pressures there may be right to left shunt across the PFO, which can be easily missed unless one has a high index of suspicion for it. Case Report: A 65-year-old white woman was transferred from surgical services to coronary care unit (CCU) following an ST-elevation inferior wall and right ventricular myocardial infarction with hypotension and respiratory failure. The patient received thrombolysis and improved over the next few days. However, even though all parameters pointed toward an upward trend in terms of improvement, it was difficult to wean the patient off the ventilator. She continued to require increasing oxygen concentration to maintain her saturation, and even at a FiO2 of 80%, her saturations were only in the range of 88-90%. She had no evidence of pulmonary embolism, pneumonia, or any other apparent causes that could have explained her large A-a gradient. At that point echocardiography was done with agitated saline bubble contrast, which demonstrated a large PFO, giving rise to a large right to left shunt. That explained her desaturation and her intolerance to weaning. No aggressive measures were taken at that time, but in the next 2 days, as the patient came out of failure, it was possible to take her off the ventilator. Teaching Point: It is important to remember that in the setting of right ventricular failure, it is prudent to keep in mind the possibility of an undiagnosed PFO any time we are trying to explain hypoxia or desaturation. Diagnosis can be made with simple bedside echocardiogram with saline bubble contrast study. It might also save extensive work-up for other causes of hypoxia in this setting.